A first phylogenetic appraisal of two allied genera of Afrotropical Ceratocanthinae: Melanophilharmostes and Pseudopterorthochaetes (Coleoptera: Hybosoridae) - Ballerio, Alberto (Fragmenta entomologica, 2016)
Two genera of Ceratocanthinae (Coleoptera Scarabaeoidea Hybosoridae), Melanophilharmostes Paulian, 1968 and Pseudopterorthochaetes Paulian, 1977, are evaluated through a cladistic morphological approach, resulting in the transfer of Melanophilharmostes demirei Paulian, 1977 to Pseudopterorthochaetes. All species are catalogued and all except two are keyed. Three new species are described: Melanophilharmostes poggii n. sp. from Annobon island (Ecuatorial Guinea), Pseudopterorthochaetes genierorum n. sp. and P. miomboincola n. sp., both from Mozambique. Melanophilharmostes zicsii (Paulian, 1968) is recorded for the first time for Burkina Faso, marking the northernmost record for African Ceratocanthinae. The records in Sudanian savannas and Miombo woodlands extend the ecological range of the subfamily.